Do swimmers conform to criterion speed during pace-controlled swimming in a 25-m pool using a visual light pacer?. Issue 6 (18th August 2021) - Gonjo, Tomohiro; McCabe, Carla; Coleman, Simon; Soares, Susana; Fernandes, Ricardo J.; Vilas-Boas, João Paulo; Sanders, Ross
ABSTRACT: The purpose of this study was to investigate whether swimmers follow the instructed speed ( v target ) accurately with the aid of a commercial visual light pacer during front crawl and backstroke swimming in a 25 m pool. Ten male swimmers performed 50 m front crawl and backstroke at different speeds (controlled by a visual light pacer) in a 25 m pool. The mean speed during the 50 m swimming ( vS ) was quantified from the time measured by a stopwatch. The mean speed of the centre of mass during a stroke cycle in the middle of the pool ( v COM ) was calculated from three-dimensional coordinates obtained from Direct Linear Transformation of two-dimensional digitised coordinates of 19 segment endpoints for each of six cameras. Swimmers achieved accurate vS in front crawl and backstroke (ICC = 0.972 and 0.978, respectively). However, v COM for the single mid-pool sample had lower correlations with v target (ICC = 0.781 and 0.681, respectively). In backstroke, v COM was slower by 4.1–5.1% than v target . However, this was not the case in front crawl (1.0–2.7%). With the use of a visual light pacer, swimmers can achieve accurate mean speed overall but are less able to achieve the target speed stroke by stroke.